Pengukuran Viskositas beberapa Produk Minyak Goreng Kelapa Sawit setelah Pemanasan - Elin Yusibani; Nursabila Al Hazmi; Evi Yufita (Agricultural Faculty, 2017)
Measurement of palm oil viscosity after heat treatment has been done. The sample is palm oil packaging and bulk ones Falling body method is used as an instrument to determine the coefficient of viscosity which had previously been calibrated using water and REFPROP. The measurement results showed that the coefficient of viscosity of palm cooking oil that has been used 10 times for 30 minuted will rise by 76% for oil packs A and about 45% for a sample of bulk, respectively. For palm oil used once but its has been using for one hour, the viscosity will be comparable to 6 times the use of the cooking oil used for 30 minutes. Thus based on the masurement of viscosity value, the palm oil will have a viscosity values are relatively small when used often, but in a short time than is used only once, but in a relatively longer.